THE USE OF BLOG MEDIA ON THE ABILITY TO WRITE SHORT STORIES BY CLASS XI STUDENTS SMA NEGERI 1 SIMPANG KANAN - Suhermi, Suhermi; Juwita, Putri (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
The purpose of this study is to describe the use of blog media on the ability to write short stories of grade XI students of SMA Negeri 1 Simpang Kanan. This research method is a field quantitative research, namely: research procedures in the form of written and oral words from people and observable informant behavior. Research instruments are tools or facilities used by researchers in collecting data so that their work is easier and the results are better, in the sense that it is more careful, complete, and systematic so that it is easier to process. The data analysis technique carried out by the author is a quantitative data analysis technique, the data from this study is in the form of short story text writing for class XI SMA Negeri 1 Simpang Kanan using blog media. The results in the pretest were in the very good category (27%), the good category (48%). Meanwhile, in the results of the short story writing posttest, it was in the very good category (28%) and the good category (2%). The use of blog media on the ability to write short stories in class XI SMA NEGERI 1 SIMPANG KANAN, in accordance with the basis for decision-making in the Kolmogorov-Smirnov normality test, it can be concluded that the data is normally distributed. From each variable of 6,627 and 4,327. Based on the value of t, the tcount value < ttable 10,211 was obtained. Therefore, it can be concluded that there is a significant linear relationship between blog media on the ability to write stories, before the treatment (pretest) and blog media on the ability to write stories after the treatment (posttest).